New records of exotic land snails and slugs in Argentina - Virgillito, Marisol (2013)
We announce the presence of two species of exotic terrestrial mollusks new for Argentina: Oxychilus draparnaudi (Oxychilidae) in Buenos Aires province and Opeas (O.) pumilum (Subulinidae) in Tucumán province. New records expand further the distributions of seven other species in Argentina: Paralaoma servilis (Punctidae) and Deroceras (Agriolimax) reticulatum (Limacidae) throughout the country; in northern tropical climates, O. (O.) pumilum and Bradybaena (B.) similaris (Helicidae); in the warm central area, Theba p. pisana (Helicidae) and O. draparnaudi; in Patagonia, Limax (L.) maximus (Limacidae); and Vertigo ovata (Vertiginidae) and Hawaiia minuscula (Pristilomatidae) in northern and central Argentina. The presence of Deroceras laeve and D. agrestis (Limacidae) could not be confirmed. It is not clear if Pupisoma (Ptychopatula) dioscoricola (Vallonidae) is a native or exotic species in Argentina.